Transport phenomena in microfluidic systems - Panigrahi, Pradipta Kumar (Wiley, 2015)
Fully comprehensive introduction to the rapidly emerging area of micro systems technology Transport Phenomena in Micro Systems explores the fundamentals of the new technologies related to Micro-Electro-Mechanical Systems (MEMS). It deals with the behavior, precise control and manipulation of fluids that are geometrically constrained to a small, typically sub-millimeter, scale, such as nl, pl, fl, small size, low energy consumption, effects of the micro domain and heat transfer in the related devices. The author describes in detail and with extensive illustration micro fabrication, channel flow, transport laws, magnetophoresis, micro scale convection and micro sensors and activators, among others. This book spans multidisciplinary fields such as material science and mechanical engineering, engineering, physics, chemistry, microtechnology and biotechnology.-Brings together in one collection recent and emerging developments in this fast-growing area of micro systems -Covers multidisciplinary fields such as materials science, mechanical engineering, microtechnology and biotechnology, et al -Comprehensive coverage of analytical models in microfluidics and MEMS technology -Introduces micro fluidics applications include the development of inkjet printheads, micro-propulsion, and micro thermal technologies -Presented in a very logical format -Supplies readers with problems and solutions.